Parallel Integral Equation Based Non-overlapping DDM for Fast Solving Electromagnetic Scattering Problems with Changeable Parts - Zongjing Gu; Xunwang Zhao; Chang Zhai; Zhongchao Lin; Yu Zhang; Qi Zhang (Applied Computational Electromagnetics Society Journal (ACES), 2019)
In this paper, a parallel non-overlapping domain decomposition method (DDM) using electric field integral equation (EFIE) is proposed for fast and accurate analysis of electrically large PEC objects with changeable parts in the condition of limited resources. The approach has considered that there are null fields as well as electric current inside a metal object in the original problem, then a novel transmission condition similar to an absorbing boundary is adopted, hence the continuity of electric currents is enhanced and the convergence is further improved in the outer iterative procedure. Moreover, the coupling between different subdomains is calculated in the manner of near field to avoid the storage of the mutual impedance. Some numerical examples are given to demonstrate the efficiency and stability of the proposed method.